PENGARUH LATIHAN LARI ZIG-ZAG TERHADAP KELINCAHAN OLAHRAGA BULUTANGKIS SISWI SMP NEGERI 25 PEKANBARU YANG MENGIKUTI EKTRAKURIKULER BULUTANGKIS - Theresia Sinaga; Slamet Slamet; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstrack: One form of training to increase agility is the Zig-zag Running exercise. In this study, researchers focused on Zigzag Running exercises. After it is formulated, the objective of this research is to find out whether there is an effect of Zig-Zag Running Exercise on the Agility of Badminton in Pekanbaru 25 Junior High School Students Who Follow Extracurricular Badminton. The design of this study is the pree test post test one group design which is done by taking the initial data of the pree test by conducting the Agilit-t Test, Widiastuti (2011). to see whether there is an effect of zig-zag running training on the agility of badminton in SMP Negeri 25 Pekanbaru students who take part in badminton extracurricular activities. The data has been obtained quantitatively and analyzed descriptively, then the hypothesis test is then carried out from research that has been conducted in accordance with the problem, namely: There is a Significant Effect of Running Exercise Zig-Zag (X) with Agility (Y). Based on the analysis of the t-test resulted in tcount of 4.390 and ttable of 2.015. So that t> t table then Ho is rejected and Ha is accepted. Based on the findings and data processing above, it can be concluded as follows: there is a significant influence between zig-zag (X) Running exercises on the Agility (Y) of SMP Negeri 25 Pekanbaru students who take part in badminton extracurricular activities. It is hoped that this research will be useful as input for developing Badminton training strategies to improve agility when receiving balls from opponents. Key Words: Zig-Zag Running Training, Agility